CHARACTERIZATION OF A STRUCTURE- BORNE SOURCE USING THE RECEPTION PLATE METHOD - Putra, Azma; Fariza, Noor; Ramlan, Roszaidi (Universiti Teknikal Malaysia Melaka, 2012)
This paper presents the characterization of vibration strength obtained from reception plate method by applying the mobility concepts. It describes a laboratorybased measurement procedure, which determines the strength of a vibration source in terms of the total squared free velocity of the source. The source used in the experiment is the small electric fan motor installed on high mobility aluminum panel in order to neglect the influence of the source mobility. The complexity of the mobility at the contact points are reduced using the single value of effective mobility. The aim is to validate the data obtained from the reception plate method with one from the direct measurement. Thus, this research is expected to give a simple but accurate way to determine input power from a structure-borne sound source.